2015
DOI: 10.3109/1061186x.2015.1055568
|View full text |Cite
|
Sign up to set email alerts
|

A novel antibody–drug conjugate anti-CD19(Fab)-LDM in the treatment of B-cell non-Hodgkin lymphoma xenografts with enhanced anticancer activity

Abstract: The present study demonstrated that the genetically engineered antibody anti-CD19(Fab)-LDM exhibited enhanced cytotoxicity compared to LDM alone. One of the most powerful advantages of anti-CD19(Fab)-LDM, however, is that it can be internalized within the cells and carry out cytotoxic effects. Therefore, anti-CD19(Fab)-LDM may be as a useful targeted therapy for B-cell lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…An increasing body of evidence suggests that aberrant microRNA expression enhances the development of drug resistance by interfering with the expression of target proteins that may be drug transporters, drug targets, or cell apoptosis- and cell-cycle-related components, resulting in cells with different degrees of sensitivity to chemotherapeutic drugs. Studies have showed that miRNAs such as miR-27a [ 3 ], miR-106a [ 4 ], miR-133a [ 5 ], miR-145 [ 6 ], miR-181b [ 7 ], miR-218 [ 8 ], and miR-326 [ 5 ] may be involved in the development of drug resistance by regulating relative gene expression. ABCB1 encodes a multi-drug-resistance gene ( MDR1 ), and is the most prominent member of the ABC transporter family, and it is the most thoroughly investigated member of this family [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing body of evidence suggests that aberrant microRNA expression enhances the development of drug resistance by interfering with the expression of target proteins that may be drug transporters, drug targets, or cell apoptosis- and cell-cycle-related components, resulting in cells with different degrees of sensitivity to chemotherapeutic drugs. Studies have showed that miRNAs such as miR-27a [ 3 ], miR-106a [ 4 ], miR-133a [ 5 ], miR-145 [ 6 ], miR-181b [ 7 ], miR-218 [ 8 ], and miR-326 [ 5 ] may be involved in the development of drug resistance by regulating relative gene expression. ABCB1 encodes a multi-drug-resistance gene ( MDR1 ), and is the most prominent member of the ABC transporter family, and it is the most thoroughly investigated member of this family [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments in our laboratory showed that the engineered fusion protein anti-CD19(Fab)-LDM exerted significant cytotoxic effects on BJAB cells (23). We performed the MTT assay to ascertain the cytotoxic effect of anti-CD19(Fab)-LDM toward BJAB/ADR cells.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that anti-CD19(Fab)-LDM suppresses tumor growth in a human B-cell lymphoma xenograft model (23). To assess whether the observed anti-CD19(Fab)-LDM-mediated inhibition of cell growth of MDR cells in vitro would extend to animal models, we established BJAB and BJAB/ADR xenograft tumor mouse models to investigate the MDR phenomenon in vivo to investigate the therapeutic effect of anti-CD19(Fab)-LDM on the BJAB/ADR xenograft model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations